Small group classes with pregnancy cadres (kekasih) can improve knowledge and attitudes about exclusive breastfeeding among third-trimester pregnant women on the remote Island of Enggano, Bengkulu Province - Yorita, Epti; Yanniarti, Sri; Yulinda, Yulinda; Pasaribu, Saur Sariaty; Rina, Rina (Alma Ata University Press, 2024)
Background: One of the government programs that focuses on the first 1000 days of life is exclusive breastfeeding for infants aged 0-6 months, but there is often a failure of exclusive breastfeeding at the age of 0-3 days due to pre-lactal feeding, so education during pregnancy is needed to improve the knowledge and attitudes of pregnant women through KEKASIH (Small Group of Cadres with Pregnant Women) classes. Objectives: This study aims to determine the effectiveness of KEKASIH classes on knowledge and attitudes of pregnant women trimester III in remote areas of Enggano Island, Bengkulu Province in 2023.Methods: Quasi-experimental research design with pre- and post-test and control group. Intervention in the form of KEKASIH class, which is a modified class for pregnant women divided into small groups with cadres as facilitators. Independent variables were KEKASIH class, dependent variables were knowledge and attitude. External variables are age, parity, education, distance of pregnancy, employment. The sample was trimester III pregnant women a total of 50 people consisting of the treatrimesterent group is pregnant women in KEKASIH class, the control group is pregnant women who receive conventional health promotion.Results:The results of the study showed that there was a difference in the mean knowledge score before and after exclusive breastfeeding education through KEKASIH class from 27.36 to 49.04, p=0.00. There is no difference in the mean attitude score before and after exclusive breastfeeding education in the control group from 28.16 to 28.96 p=0.00.Conclusions: KEKASIH Class is more effective in improving mothers' knowledge and attitudes about exclusive breastfeeding with a value of p=00. Educational factors affect mothers' knowledge, but gestational distance and parity affect mothers' attitudes about exclusive breastfeeding.